Case report: A rare case of triple negative breast cancer with development of acute pancreatitis due to dexamethasone during adjuvant chemotherapy - Ohmura, Hirofumi; Tobo, Taro; Ando, Yuki; Masuda, Takaaki; Mimori, Koshi; Akashi, Koichi; Baba, Eishi (Frontiers in Oncology, 2024)
Here, we present the case of a 42-year-old female who developed acute pancreatitis due to dexamethasone during adjuvant chemotherapy for early triple negative breast cancer (TNBC). The patient received partial mastectomy and sentinel lymph node biopsy for early TNBC (cT1N0M0, cStage I) of the left breast. Dose-dense doxorubicin plus cyclophosphamide (ddAC) was administered as the adjuvant-chemotherapy; however, epigastralgia appeared on the fifth day of the first administration. A blood test showed a remarkable increase of serum pancreatic enzyme levels and computed tomography (CT) showed the swelling of pancreas and surrounding effusion, and she was diagnosed with moderate acute pancreatitis. As she had no history of excessive alcohol consumption or complication of cholelithiasis, dyslipidemia, or pancreatic neoplasm, drug-induced pancreatitis was suspected. Dexamethasone, which was administered as an antiemetic, was the suspected drug based on the drug administration history and previous report, and dexamethasone was discontinued from the second administration of ddAC. There was subsequently no recurrence of pancreatitis with no increase in serum pancreatic enzyme levels, and it was possible to complete adjuvant-chemotherapy. Alcohol, gallstones, dyslipidemia, and drugs have been reported as causes of pancreatitis; however, steroid-induced acute pancreatitis is extremely rare. We present the first case of acute pancreatitis induced by dexamethasone as the antiemetic.